2004
DOI: 10.1016/j.bbmt.2004.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct phases in recovery of reconstituted innate cellular-mediated immunity after murine syngeneic bone marrow transplantation

Abstract: Defects in immune reconstitution after hematopoietic stem cell transplantation confer extreme infection risk on to the transplant recipient. Perturbations in adaptive immune reconstitution have been well characterized, yet defects in reconstituted innate cellular-mediated immunity remain largely unstudied. Recovery in innate effector cells was defined by using an established murine model of autologous bone marrow transplantation. Cytokine induction after cell culture and systemic stimulation with pathogen-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 72 publications
0
22
0
1
Order By: Relevance
“…That is, studies have shown that host cells including T cells 294 and DCs 50,53 are present in the early post transplant period. In addition, BM stromal and mesenchymal stem cells remain host in origin for years after successful donor-derived hematopoietic engraftment.…”
Section: Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…That is, studies have shown that host cells including T cells 294 and DCs 50,53 are present in the early post transplant period. In addition, BM stromal and mesenchymal stem cells remain host in origin for years after successful donor-derived hematopoietic engraftment.…”
Section: Future Directionsmentioning
confidence: 99%
“…295,296 In what capacity these host cells influence donor-derived hematopoietic and immune recovery remains to be defined. However, these host-derived immune effector cells do contribute to inflammatory responses in the post transplant period; 53 and their presence has implications with respect to risk for relapse disease 297 and anti-microbial responses. 298 Therefore, further study is warranted to define if hostderived immune cells modulate effects on donor-derived hematopoiesis and immune recovery.…”
Section: Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There are some conflicting studies as to the functional ability of PMNs post-HSCT. Researchers found that reconstituted PMNs had diminished or impaired chemotaxis, superoxide production, and bactericidal activity for at least two months after allogeneic HSCT [5]. Similarly, impairment in chemotaxis, superoxide induction, and phagocytic function was found months to years post-transplant in PMNs from patients receiving autologous transplants [106].…”
Section: Pmn Reconstitutionmentioning
confidence: 99%
“…Peripheral phagocytes and NK cells are the first cells to be reconstituted post-HSCT in human transplant recipients [5,61]. After the initial reestablishment of phagocytes, there is repopulation of early lymphoid cells responsible first for primitive and then for more specific functions, such as proliferation, helper activity, differentiation, cytokine production, and antibody synthesis [61].…”
Section: Innate Immune Reconstitutionmentioning
confidence: 99%